SPECIAL EDUCATION TEACHERS’ ABILITY IN LITERACY AND NUMERACY ASSESSMENTS BASED ON LOCAL WISDOM - Citrawan, I Wayan; Widana, I Wayan; Sumandya, I Wayan; Widana, I Nengah Suka; Mukminin, Amirul; Arief, Hanief; Razak, Rafiza Abdul; Hadiana, Deni; Meter, Wayan (Jurnal Ilmiah Ilmu Terapan Universitas Jambi, 2024)
This pioneering research endeavors to delve into the competencies of special education teachers in Indonesia concerning the development of literacy and numeracy assessments rooted in local wisdom, while simultaneously exploring the fundamental concepts of evaluation and teacher responsibilities. Employing a mixed-method explanatory design, the study represents a novel approach to understanding the intricate interplay between pedagogical practices and cultural contexts. Drawing upon a diverse research population comprising special education teachers across Indonesia, the quantitative component of the study employs a rigorous proportional random sampling method, culminating in a robust sample size of 457 participants. Meanwhile, the qualitative inquiry adopts purposive and snowball sampling techniques to ensure a comprehensive exploration of teachers' perspectives and experiences. Research data, spanning questionnaires, interviews, observations, and document analyses, are meticulously collected and analyzed using innovative methodological frameworks such as Confirmatory Factor Analysis (CFA) and variance-based Structural Equation Modeling (SEM) for quantitative data, and data reduction, display, and conclusion for qualitative data. Findings underscore the nuanced variations in teachers' competencies across different regions, with Bali emphasizing the basic concept of evaluation, NTB Province prioritizing teacher responsibility, and NTT Province echoing similar sentiments. This research not only sheds light on the unique challenges and opportunities encountered by special education teachers but also offers invaluable insights into the integration of local wisdom in assessment development, paving the way for more culturally responsive and effective educational practices in Indonesia and beyond.